Inovasi Teknologi Pembuatan Pakan Ayam Broiler Berbasis Bahan Baku Lokal - Mastur; Ashari; I K Sumadi; I GNG Bidura; Bulkaini (Universitas Mataram, 2021)
The innovation of feed manufacturing technology is an innovation that can process pineapple peel waste into poultry feed by applying facultative anaerobic fermentation technology. The purpose of implementing this technological innovation is to optimize the use of several local raw materials (bran, milled corn and fermented pineapple peel) into poultry feed through the Partner Village Empowerment Program (PPDM) in 2021. This activity has been carried out in Sigar Penjalin Village in partnership with the group. youth mosque